PEMETAAN SEBARAN SPASIAL KUALITAS AIR UNSUR HARA PERAIRAN TELUK LAMPUNG - Yulianto, Herman (AQUASAINS, 2013)
Lampung Bay plays an importantrole for the terestriel area that surroundsit. Run Of any river that containdomestic waste into the Lampung Bayhas threatened the water quality condition.The purpose of the research is to analyzewater quality and nutrient horizontal distributionin Lampung Bay.This research washeld in April 2012, where spatial and temporalsurvey methods was used in this researchby performing a direct physical andchemical measurement. The results showeda range of water quality and nutrient compositionin the Lampung Bay as follows:temperature 28.9 - 31oC, depth 13 - 42,8m, visibility 5 - 16.5 m, Current speed 5 -35 m/s, pH 8.02 - 8.64, salinity 33o/oo, SuspendedSolid 27 - 86 mg/l, Dissolve oxygen4,62 - 6.78 mg/l, Nitrate 0.002 - 0.38 mg/land phosphat 0.01 - 0.48 mg/l. At Overall,nutrient composition shown a narrowrange, however condition of water qualitystill in normal condition